Fe3O4 (at) SiO2 (at) UiO-66-NH2 (at) PPL spherical core-shell magnetic composite material, preparation method and toxin degradation method
Through the use of Fe3O4@SiO2@UiO-66-NH2@PPL spherical core-shell magnetic composite materials, the problems of low degradation efficiency of food toxins and cumbersome recycling steps in the prior art are solved, and efficient and stable toxin degradation and efficient separation are achieved. , improves food safety and environmental protection.
Patent Information
- Application Number
- CN202411191418.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-28
- Publication Date
- 2024-12-13
AI Technical Summary
The prior art uses porcine pancreatic lipase or metal organic framework to remove food toxins, and the degradation efficiency is low, and the recycling steps of porcine pancreatic lipase are cumbersome and the reuse rate is low.
Fe3O4@SiO2@UiO-66-NH2@PPL spherical core-shell magnetic composite material is used to connect zirconium ions to Fe3O4@SiO2 nanoparticles and modify amino groups to fix porcine pancreatic lipase to form Fe3O4@SiO2@UiO-66- NH2@PPL spherical core-shell magnetic composite material to improve the adsorption and degradation ability of penicillin and ochratoxin A, and to simplify the recycling process by using the separation characteristics of the magnetic material.
The efficient degradation of penicillin and ochratoxin A was achieved, with degradation rates reaching 77.03% and 85.48%, and the reusability of materials was improved, processing costs and impact on the natural flavor of food.
Smart Images

Figure CN119111723A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of mycotoxins and relates to toxin degradation, and specifically relates to a Fe3O4@SiO2@UiO-66-NH2@PPL spherical core-shell magnetic composite material, a preparation method and a method for degrading toxins. Background Art
[0002] Patulin (PAT) is a secondary metabolite mainly produced by Penicillium expansum. It is the most important mycotoxin in fruits, especially apples and apple products. Eating food contaminated with patulin can cause various acute and chronic symptoms, including headache, dizziness, liver and kidney damage, pulmonary and cerebral edema, etc. It is genotoxic, teratogenic and carcinogenic. Ochratoxin A (OTA) is a fungal secondary metabolite that is widely present in grains and fruits contaminated by Aspergillus and Penicillium, posing a huge threat to human health. OTA is genotoxic, nephrotoxic, carcinogenic, teratogenic, immunosuppressive and hepatotoxic, and is a potential safety hazard for grape juice and other grape products. Therefore, degrading and removing food toxins is crucial for food safety.
[0003] At present, the methods for degrading food toxins are mainly divided into physical methods, chemical methods and biological enzymatic methods. Among them, the physical method uses ultraviolet irradiation or ultra-high temperature sterilization to remove PAT and OTA, and the removal effect of this method is not good. The chemical method uses chemical reagents (such as acids, chlorides, oxidants and salt compounds) to degrade PAT and OTA. The main defects of this method include: unstable effect, high processing cost, and it will affect the natural flavor of food.
[0004] Compared with physical and chemical methods, bio-enzymatic hydrolysis has the advantages of substrate-specific detoxification efficiency, and this method has less risk to health and the environment, and is becoming an effective way to replace traditional mycotoxin removal methods. Porcine pancreatic lipase (PPL) is the most widely used enzyme in biocatalytic reactions. Porcine pancreatic lipase has a wide range of substrates and exhibits great regional and enantioselectivity and specificity.
[0005] Metal organic frameworks (MOFs) have been gradually applied to the adsorption and degradation of environmental pollutants and food toxins in recent years due to their outstanding advantages such as large specific surface area, diverse structures, adjustable pore size, low density, controllable pore function, suitable adsorption capacity, and easy synthesis. Among them, zirconium-based metal organic frameworks (Zr-MOFs) have good chemical stability and thermal stability, especially good structural stability in aqueous media, which is better than most MOFs. UiO-66 is a typical Zr-MOFs, which has excellent hydrophilicity and is easily dispersed in aqueous media and captures organic pollutants. In addition, it is easy to introduce other structures into UiO-66, which is conducive to post-synthesis modification.
[0006] The existing technologies for removing food toxins based on bio-enzymatic hydrolysis and MOFs have the following main defects: First, the single porcine pancreatic lipase or MOFs has weak adsorption and binding ability to patulin and ochratoxin A, so the degradation efficiency is low. Second, the recovery step of porcine pancreatic lipase after degradation is relatively cumbersome, requiring centrifugation, and the recovery rate is not high, so the reuse rate is low. Summary of the invention
[0007] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a Fe3O4@SiO2@UiO-66-NH2@PPL spherical core-shell magnetic composite material, a preparation method and a method thereof, so as to solve the technical problem of low degradation efficiency when using porcine pancreatic lipase or MOFs to remove food toxins in the prior art.
[0008] In order to solve the above technical problems, the present invention adopts the following technical solutions to achieve the above problems:
[0009] A method for degrading toxins, the method uses Fe3O4@SiO2@UiO-66-NH2@PPL spherical core-shell magnetic composite material to degrade toxins. The toxin is a mixed toxin composed of patulin and ochratoxin A. The Fe3O4@SiO2@UiO-66-NH2@PPL spherical core-shell magnetic composite material is composed of Fe3O4@SiO2@UiO-66-NH2 material and porcine pancreatic lipase; the Fe3O4@SiO2@UiO-66-NH2 material uses Fe3O4@SiO2 nanoparticles as a carrier, and the carrier is loaded with zirconium and modified with amino groups.
[0010] The present invention also has the following technical features:
[0011] Specifically and preferably, the mass ratio of the Fe3O4@SiO2@UiO-66-NH2 material and porcine pancreatic lipase is (1:3) to (3:1), and most preferably is 1:1.
[0012] Specifically and preferably, the mass ratio of the Fe3O4@SiO2@UiO-66-NH2@PPL spherical core-shell magnetic composite material, patulin, and ochratoxin A is (10-20): (0.005-0.04): (0.005-0.04), and the most preferred ratio is 10:0.008:0.008.
[0013] The method specifically comprises the following steps:
[0014] Step 1, preparing Fe3O4@SiO2@UiO-66-NH2@PPL spherical core-shell magnetic composite material;
[0015] Step 2: Degradation of mixed toxins:
[0016] The mother liquor of ochratoxin A is taken and slowly dried with nitrogen, and then dissolved with grape juice; the mother liquor of patulin is taken and slowly dried with nitrogen, and then dissolved with apple juice; then the apple juice containing patulin and the grape juice containing ochratoxin A are mixed to obtain juice containing mixed toxins; finally, the Fe3O4@SiO2@UiO-66-NH2@PPL spherical core-shell magnetic composite material is added to the juice containing mixed toxins, and then incubated on a vortex oscillator, the incubation temperature is 20°C, the incubation speed is 100-300rpm, preferably 180rpm, and the incubation time is 72 hours.
[0017] Optionally, when the toxin is a single ochratoxin A, the method specifically comprises the following steps:
[0018] Step 1, preparing Fe3O4@SiO2@UiO-66-NH2@PPL spherical core-shell magnetic composite material;
[0019] Step 2: Degradation of ochratoxin A:
[0020] The mother liquor of ochratoxin A is taken and slowly dried with nitrogen, then dissolved with grape juice, and then the Fe3O4@SiO2@UiO-66-NH2@PPL spherical core-shell magnetic composite material is added to the grape juice containing ochratoxin A, and then incubated on a vortex oscillator, the incubation temperature is 15-40°C, preferably 20-25°C; the incubation speed is 100-300rpm, most preferably 180rpm; the incubation time is 72 hours.
[0021] Specifically and preferably, the mass ratio of the Fe3O4@SiO2@UiO-66-NH2@PPL spherical core-shell magnetic composite material and ochratoxin A is (10-20): (0.005-0.04), and most preferably (10-20): (0.008-0.04).
[0022] Specifically, the preparation method of the Fe3O4@SiO2@UiO-66-NH2@PPL spherical core-shell magnetic composite material comprises the following steps:
[0023] Step 1.1, preparation of Fe3O4@SiO2 nanoparticles:
[0024] The Fe3O4 nanoparticles were ultrasonically dispersed in distilled water, and then ammonia and ethanol were added and stirred to obtain an iron precursor mixture; ethyl tetrasilicate was dissolved in ethanol and stirred until the mixture was uniform to obtain an ethyl tetrasilicate solution; the ethyl tetrasilicate solution was added to the iron precursor mixture and stirred, and then the solution was separated by an external magnet and washed with distilled water and ethanol several times to obtain Fe3O4@SiO2 nanoparticles, and finally the Fe3O4@SiO2 nanoparticles were dried.
[0025] Step 1.2, preparation of Fe3O4@SiO2@UiO-66-NH2 material:
[0026] The Fe3O4@SiO2 nanoparticles, zirconium chloride and water prepared in step 1.1 are added to N, N-dimethylformamide and stirred to obtain an iron-zirconium precursor mixture; 2,5-diaminoterephthalic acid is added to N, N-dimethylformamide to obtain a 2,5-diaminoterephthalic acid solution; the iron-zirconium precursor mixture and the 2,5-diaminoterephthalic acid solution are mixed and stirred continuously until they are completely dissolved, and then the mixed system is heated at 120°C for 24 hours, taken out, cooled to room temperature, and washed with water to obtain a Fe3O4@SiO2@UiO-66-NH2 material, and finally the Fe3O4@SiO2@UiO-66-NH2 material is dried;
[0027] Step 1.3, Immobilization of Porcine Pancreatic Lipase:
[0028] The Fe3O4@SiO2@UiO-66-NH2 material prepared in step 1.2, porcine pancreatic lipase and phosphate buffer solution were mixed; the mixture was then shaken at 20°C for 5 to 15 hours, then taken out, filtered and the solid product was collected; finally, the solid product was washed with phosphate buffer solution and freeze-dried overnight to obtain Fe3O4@SiO2@UiO-66-NH2@PPL spherical core-shell magnetic composite material.
[0029] Specifically, in step 1.1, the mass ratio of Fe3O4 nanoparticles to ethyl tetrasilicate is 0.1:2.85.
[0030] Specifically, in step 1.2, the mass ratio of Fe3O4@SiO2 nanoparticles, zirconium chloride and 2,5-diaminoterephthalic acid is 1:2:2.
[0031] The present invention also protects a Fe3O4@SiO2@UiO-66-NH2@PPL spherical core-shell magnetic composite material as described above; the BET specific surface area of the composite material is 11.996 m 2 / g, pore volume is 0.061cm 2 / g, the pore volume is 10.786nm, and the average particle size is 500.167nm.
[0032] The present invention also protects a method for preparing the Fe3O4@SiO2@UiO-66-NH2@PPL spherical core-shell magnetic composite material as described above.
[0033] Compared with the prior art, the present invention has the following technical effects:
[0034] The present invention connects zirconium ions to Fe3O4@SiO2 nanoparticles and modifies them with amino groups to obtain Fe3O4@SiO2@UiO-66-NH2 materials; then, porcine pancreatic lipase is fixed on the Fe3O4@SiO2@UiO-66-NH2 material to obtain Fe3O4@SiO2@UiO-66-NH2@PPL spherical core-shell magnetic composite materials. Patulin and ochratoxin A contain highly reactive electrophilic groups that can covalently bond with amino groups (-NH2), thereby improving the material's ability to adsorb and degrade toxins. In addition, because the composite material is magnetic, it can be efficiently and quickly separated under the action of external magnetism, and no centrifugation or other operations are required during recovery, so it has high reusability.
[0035] The Fe3O4@SiO2@UiO-66-NH2@PPL spherical core-shell magnetic composite material of the present invention can achieve a maximum degradation rate of 77.03% for single patulin, a degradation rate of 85.48% for patulin in mixed toxins, a degradation rate of 35.62% for patulin in mixed toxins, and a degradation rate of 47.67% for patulin in mixed toxins, thereby achieving efficient degradation of mixed toxins and single toxins.
[0036] In summary, the present invention combines the advantages of biodegradation and magnetic materials, has the characteristics of high efficiency, stability, safety and easy separation, and provides a new solution for preparing a low-cost and environmentally friendly fungal mycotoxin biodetoxification system. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] Figure 1 This is a scanning electron microscope image. Figure 1 Middle: (a) is the scanning electron microscope image of Fe3O4 nanoparticles; (b) is the scanning electron microscope image of Fe3O4@SiO2 nanoparticles; (b) is the scanning electron microscope image of Fe3O4@SiO2 nanoparticles; (d) is the scanning electron microscope image of Fe3O4@SiO2@UiO-66 particles; (e) is the scanning electron microscope image of Fe3O4@SiO2@UiO-66-NH2 material; (e) is the scanning electron microscope image of Fe3O4@SiO2@UiO-66-NH2@PPL spherical core-shell magnetic composite material.
[0038] Figure 2 Transmission electron microscopy image. Figure 2 Middle: (a) is the transmission electron microscopy image of Fe3O4@SiO2@UiO-66-NH2 material; (b) is the transmission electron microscopy image of Fe3O4@SiO2@UiO-66-NH2@PPL spherical core-shell magnetic composite material.
[0039] Figure 3This is the dispersion X-ray spectrum of Fe3O4@SiO2@UiO-66-NH2@PPL spherical core-shell magnetic composite material. Figure 3 Middle: (a) and (b) show the Fe3O4@SiO2@UiO-66-NH2@PPL spherical core-shell magnetic composites under different light sources, (c) to (h) show the distribution of carbon (C), oxygen (O), silicon (Si), nitrogen (N), zirconium (Zr), and iron (Fe) in the Fe3O4@SiO2@UiO-66-NH2@PPL spherical core-shell magnetic composites.
[0040] Figure 4 These are the X-ray diffraction results of Fe3O4 nanoparticles, Fe3O4@SiO2 nanoparticles, Fe3O4@SiO2@UiO-66 particles, Fe3O4@SiO2@UiO-66-NH2 materials, and Fe3O4@SiO2@UiO-66-NH2@PPL spherical core-shell magnetic composites.
[0041] Figure 5 These are the magnetic strength results of Fe3O4 nanoparticles, Fe3O4@SiO2 nanoparticles, Fe3O4@SiO2@UiO-66 particles, Fe3O4@SiO2@UiO-66-NH2 materials, and Fe3O4@SiO2@UiO-66-NH2@PPL spherical core-shell magnetic composites.
[0042] Figure 6 These are the infrared spectra of Fe3O4 nanoparticles, Fe3O4@SiO2 nanoparticles, Fe3O4@SiO2@UiO-66 particles, Fe3O4@SiO2@UiO-66-NH2 materials, and Fe3O4@SiO2@UiO-66-NH2@PPL spherical core-shell magnetic composites.
[0043] Figure 7 This is the X-ray electron energy spectrum of Fe3O4@SiO2@UiO-66 particles. Figure 7 Middle: (a), (b), (c), and (d) show the photoelectron spectra of the C1S orbital, Zr 1S orbital, Si 2p orbital, and O1S orbital, respectively.
[0044] Figure 8 This is the X-ray electron energy spectrum of Fe3O4@SiO2@UiO-66-NH2 material. Figure 8 Middle: (a), (b), (c), and (d) show the photoelectron spectra of C1S orbital, Zr 3d orbital, Si 2p orbital, N 1s orbital, and O1S orbital, respectively.
[0045] Fig. 9This is the X-ray electron energy spectrum of Fe3O4@SiO2@UiO-66-NH2@PPL spherical core-shell magnetic composite material. Fig. 9 Middle: (a), (b), (c), and (d) show the photoelectron spectra of C1S orbital, Zr 3d orbital, Si 2p orbital, N 1s orbital, and O1S orbital, respectively.
[0046] Fig.10 This is the nitrogen adsorption-desorption isotherm of Fe3O4@SiO2@UiO-66-NH2@PPL spherical core-shell magnetic composite material.
[0047] Fig.11 The degradation results of single ochratoxin A by Fe3O4@SiO2@UiO-66-NH2@PPL spherical core-shell magnetic composites are shown as the degradation time changes. Fig.11 Middle: (a) is the degradation curve.
[0048] (b) is the regression curve.
[0049] Fig.12 The degradation results of single ochratoxin A by Fe3O4@SiO2@UiO-66-NH2@PPL spherical core-shell magnetic composites were shown under different immobilization times of porcine pancreatic lipase. Fig.12 Middle: (a) is the degradation curve. (b) is the regression curve.
[0050] Fig.13 The degradation results of single ochratoxin A by Fe3O4@SiO2@UiO-66-NH2@PPL spherical core-shell magnetic composites at different incubation degradation temperatures are shown. Fig.13 Middle: (a) is the degradation curve. (b) is the regression curve.
[0051] Fig.14 The degradation results of the mixed toxins composed of patulin (PAT) and ochratoxin A (OTA) by Fe3O4@SiO2@UiO-66-NH2@PPL spherical core-shell magnetic composites are shown.
[0052] The specific contents of the present invention are further explained in detail below in conjunction with embodiments. DETAILED DESCRIPTION
[0053] It should be noted that all reagents, kits, raw materials and detection methods used in the present invention, unless otherwise specified, are reagents, kits, raw materials and detection methods known in the art.
[0054] Specific embodiments of the present invention are given below. It should be noted that the present invention is not limited to the following specific embodiments, and all equivalent changes made on the basis of the technical solution of this application fall within the protection scope of the present invention.
[0055] Embodiment 1:
[0056] This embodiment provides a method for preparing a Fe3O4@SiO2@UiO-66-NH2@PPL spherical core-shell magnetic composite material, which specifically includes the following steps:
[0057] Step 1.1, preparation of Fe3O4@SiO2:
[0058] In this embodiment, step 1.1 is exactly the same as step 1.1 of embodiment 1.
[0059] Step 1.2, preparation of Fe3O4@SiO2@UiO-66-NH2:
[0060] 150 mg of Fe3O4@SiO2, 300 mg of zirconium chloride and 75 uL of water were added to 20 mL of N, N-dimethylformamide (DMF) and stirred for 15 min to obtain an iron-zirconium precursor mixture; 300 mg of 2-aminoterephthalic acid was added to 10 mL of DMF to obtain a 2-aminoterephthalic acid solution; the iron-zirconium precursor mixture and the 2-aminoterephthalic acid solution were mixed and continued to be stirred until they were completely dissolved; the above system was transferred to an autoclave, heated at 120°C for 24 h, taken out, cooled to room temperature, and washed with ultrapure water 5 times to obtain a brown magnetic product, namely Fe3O4@SiO2@UiO-66-NH2; finally, Fe3O4@SiO2@UiO-66-NH2 was dried in an oven at 50°C overnight.
[0061] Step 1.3, Immobilization of Porcine Pancreatic Lipase:
[0062] 100 mg of freshly prepared Fe3O4@SiO2@UiO-66-NH2 and porcine pancreatic lipase were mixed with 15 mL of phosphate buffer solution (PBS, pH 7.0), and the mass ratios of Fe3O4@SiO2@UiO-66-NH2 and porcine pancreatic lipase were 3:1, 2:1, 1:1, 1:2, and 1:3; the above mixture was shaken and cultured on a shaker at 20°C for 10 h, then taken out and the solid product was filtered and collected. The solid product was washed 8 times with PBS and freeze-dried overnight to obtain Fe3O4@SiO2@UiO-66-NH2@PPL spherical core-shell magnetic composite material.
[0063] Embodiment 2:
[0064] This embodiment provides a method for preparing a Fe3O4@SiO2@UiO-66-NH2@PPL spherical core-shell magnetic composite material. The method is basically the same as that of Example 3, except that step 1.3 is different.
[0065] In this embodiment, step 1.3 is specifically as follows: 100 mg of freshly prepared Fe3O4@SiO2@UiO-66-NH2 and porcine pancreatic lipase are mixed with 15 mL of phosphate buffer solution (PBS, pH 7.0), and the mass ratio of Fe3O4@SiO2@UiO-66-NH2 and porcine pancreatic lipase is 1:1; the above mixture is shaken and cultured on a shaker at 20°C for 5h, 7.5h, 10h, 12.5h, and 15h, then taken out, the solid product is filtered and collected, the solid product is washed 8 times with PBS, and then freeze-dried overnight to obtain a Fe3O4@SiO2@UiO-66-NH2@PPL spherical core-shell magnetic composite material.
[0066] Embodiment 3:
[0067] This embodiment provides a method for preparing a Fe3O4@SiO2@UiO-66-NH2@PPL spherical core-shell magnetic composite material. The method is basically the same as that of Example 3, except that step 1.3 is different.
[0068] In this embodiment, step 1.3 is specifically as follows: 100 mg of freshly prepared Fe3O4@SiO2@UiO-66-NH2 and porcine pancreatic lipase are mixed with 15 mL of phosphate buffer solution (PBS, pH 7.0), and the mass ratio of Fe3O4@SiO2@UiO-66-NH2 and porcine pancreatic lipase is 1:1; the above mixture is shaken and cultured on a shaker at 20°C for 10 hours, then taken out, the solid product is filtered and collected, the solid product is washed 8 times with PBS and then freeze-dried overnight to obtain Fe3O4@SiO2@UiO-66-NH2@PPL spherical core-shell magnetic composite material.
[0069] Embodiment 4:
[0070] This embodiment provides a method for degrading ochratoxin A in grape juice using the Fe3O4@SiO2@UiO-66-NH2@PPL spherical core-shell magnetic composite material prepared in Example 1. The method specifically comprises the following steps:
[0071] Step 1, preparing Fe3O4@SiO2@UiO-66-NH2@PPL spherical core-shell magnetic composite material;
[0072] Step 2: Degradation of ochratoxin A:
[0073] Take 8 mL of ochratoxin stock solution [concentration of 2 μg / mL] and slowly blow dry with nitrogen, then dissolve it with 10 mL of grape juice; then add 20 mg of Fe3O4@SiO2@UiO-66-NH2@PPL spherical core-shell magnetic composite material to the grape juice containing ochratoxin, and then incubate on a vortex oscillator with an incubation temperature of 25°C, an incubation speed of 180 rpm, and an incubation time of 0, 12, 24, 36, 48, 60, and 72 hours.
[0074] In this example, centrifugation was performed after the incubation was completed, the material was removed after centrifugation, and the supernatant was filtered using a 0.22 μm syringe filter. The obtained filtrate was placed in a brown liquid phase vial and stored at 4° C. awaiting detection.
[0075] In this embodiment, it is necessary to obtain an ochratoxin A standard curve before performing the degradation experiment to facilitate subsequent detection and quantification. The specific process of obtaining the ochratoxin A standard curve is as follows: weigh 100 mg of ochratoxin A in a 100 mL volumetric flask, dilute to the volumetric flask mark with chromatographic grade methanol, and then accurately configure ochratoxin A standard solutions with concentrations of 0.1 ug / mL, 0.5 ug / mL, 1 ug / mL, 1.5 ug / mL, and 2.0 ug / mL by stepwise dilution; use an HPLC ultraviolet detector to detect the absorbance values of the above series of ochratoxin A standard solutions, and draw an ochratoxin A standard curve according to the absorbance values and the concentration values of the patulin standard solution. The ochratoxin A standard curve equation is Y2=36966994x2+1027592 (correlation coefficient R 2 =0.9992), where: Y2 represents the peak area, and x2 represents the ochratoxin A concentration.
[0076] Embodiment 5:
[0077] This example provides a method for degrading ochratoxin A in grape juice using the Fe3O4@SiO2@UiO-66-NH2@PPL spherical core-shell magnetic composite material prepared in Example 2; this method is the same as Example 4.
[0078] Embodiment 6:
[0079] This example provides a method for degrading ochratoxin A in grape juice using the Fe3O4@SiO2@UiO-66-NH2@PPL spherical core-shell magnetic composite material prepared in Example 3; this method is basically the same as Example 4, except that step 2 is different.
[0080] In this embodiment, step 2 is specifically as follows: 8 mL of ochratoxin mother solution [concentration of 2 μg / mL] is taken and slowly dried with nitrogen, and then dissolved with 10 mL of grape juice; then 20 mg of Fe3O4@SiO2@UiO-66-NH2@PPL spherical core-shell magnetic composite material is added to the grape juice containing ochratoxin, and then incubated on a vortex oscillator, the incubation temperature is 15°C, 20°C, 25°C, 30°C, 35°C, 40°C, the incubation speed is 180 rpm, and the incubation time is 0, 12, 24, 36, 48, 60, 72 hours.
[0081] Embodiment 7:
[0082] This embodiment provides a method for degrading patulin and ochratoxin A in a mixed juice consisting of apple juice and grape juice using the Fe3O4@SiO2@UiO-66-NH2@PPL spherical core-shell magnetic composite material prepared in Example 3. The method specifically comprises the following steps:
[0083] Step 1, preparing Fe3O4@SiO2@UiO-66-NH2@PPL spherical core-shell magnetic composite material;
[0084] Step 2: Degradation of mixed toxins:
[0085] Take 4mL of ochratoxin A mother solution [concentration of 2ug / mL] and slowly blow it dry with nitrogen, then dissolve it with 5mL of grape juice; take 4mL of patulin mother solution [concentration of 2ug / mL] and slowly blow it dry with nitrogen, then dissolve it with 5mL of apple juice; then mix the apple juice containing patulin and the grape juice containing ochratoxin A to obtain juice containing mixed toxins; finally, add 20mg of Fe3O4@SiO2@UiO-66-NH2@PPL spherical core-shell magnetic composite material to the juice containing mixed toxins, and then incubate on a vortex oscillator at a temperature of 25°C, a speed of 180rpm, and incubation times of 0, 12, 24, 36, 48, 60, and 72 hours, respectively.
[0086] In this embodiment, in addition to obtaining the ochratoxin A standard curve before performing the degradation experiment, it is also necessary to obtain the patulin standard curve. The ochratoxin A is the same as in Example 4. The specific process of obtaining the patulin standard curve is as follows: weigh 100 mg of patulin in a 100 mL volumetric flask, dilute to the scale line of the volumetric flask with chromatographic grade methanol, and then accurately configure patulin standard solutions with concentrations of 1 μg / mL, 5 μg / mL, 10 μg / mL, 25 μg / mL, and 50 μg / mL by stepwise dilution; use an HPLC ultraviolet detector to detect the absorbance values of the above series of patulin standard solutions, and draw a patulin standard curve according to the absorbance values and the concentration values of the patulin standard solution. The patulin standard curve equation is Y1=96045x1+63291 (correlation coefficient R 2 =0.9999), where: Y1 represents the peak area, x1 represents the concentration of patulin.
[0087] The characterization, physicochemical properties and degradation effects of the above examples on toxins are as follows:
[0088] (A) Characterization and physicochemical properties of the Fe3O4@SiO2@UiO-66-NH2@PPL spherical core-shell magnetic composite materials prepared in Examples 1 to 3:
[0089] (1) The morphology and structure of the prepared materials were observed and the surface element distribution was analyzed by scanning electron microscopy (SEM), transmission electron microscopy (TEM) and dispersive X-ray spectroscopy (EDS). Figures 1 to 3 As shown. Figure 1 It can be seen that the diameter of Fe3O4 particles ranges from 100nm to 200nm. As the modified components increase, it can be found that the particle size of the material increases. Figure 2 It can be seen that UiO-66-NH2 and PPL successfully grew on the surface of Fe3O4 nanoparticles and aggregated. The average size of the core-shell microstructure in the composite material ranged from 150 to 200 nm, and the shell thickness was about 20 nm. Figure 3 It can be seen that the -NH2 groups are evenly distributed in the UiO-66 framework.
[0090] (2) The particle size of Fe3O4@SiO2@UiO-66-NH2@PPL spherical core-shell magnetic composites was analyzed by dynamic light scattering (DLS). The results are shown in Table 1:
[0091] Table 1. Particle size of composite materials
[0092]
[0093]
[0094] It can be seen from Table 1 that the average diameters of Fe3O4, Fe3O4@SiO2, Fe3O4@SiO2@UiO-66, Fe3O4@SiO2@UiO-66-NH2, Fe3O4@SiO2@UiO-66-NH2@PPL, and DLS analysis results are 187.33nm, 277.33nm, 333.00nm, 370.67nm, and 375.67nm, respectively. The average diameter of the particles gradually increases, indicating that SiO2 and PPL play the role of modifying enzymes.
[0095] (3) The material structure of Fe3O4@SiO2@UiO-66-NH2@PPL spherical core-shell magnetic composite material was determined by X-ray diffraction (XRD). Figure 4 As shown. Figure 4 It can be seen that the XRD patterns of UiO-66 and UiO-66-NH2 are consistent with the simulation patterns of UiO-66 and existing reports, indicating that a pure crystalline UiO-66 phase is formed in the composite material. At the same time, it was found that no significant changes were found in the main diffraction peaks between UiO-66 and UiO-66-NH2, which indicates that the crystal structure of the synthesized UiO-66 is well preserved after -SH modification. The diffraction peaks at 30.076 (220), 35.426 (311) and 43.053 (400), 56.935 (511), 62.520 (440) correspond to Fe3O4 (JCPDS PDF No. 99-0073). The composite material has the main diffraction peaks of UiO-66-NH2 and Fe3O4 at the same time, and does not show any characteristic peaks of other impurities, proving the coexistence of UiO-66-NH2 and Fe3O4 crystal phases in the nanocomposite material, and confirming that high-purity Fe3O4@SiO2@UiO-66-NH2 has been synthesized. After modifying PPL, it was found that the diffraction peaks at 31.707 (200), 45.453 (220), 56.479 (222) and 75.301 (420) correspond to NaCl (JCPDS PDF No. 99-0059), which is because the PPL solvent is PBS, thus further proving that the PPL modification is successful.
[0096] (4) The magnetic strength of the composite material was analyzed using a vibrating sample magnetometer (VSM). Figure 5 As shown. Figure 5It can be seen that the saturation magnetic field strength of Fe3O4 particles is 69.02emu / g. The saturation magnetization strengths of Fe3O4@SiO2 and Fe3O4@SiO2@UiO-66 are 32.09emu / g and 23.83emu / g, respectively. Under different modification conditions, the saturation magnetization strengths of UiO-66-NH2 and UiO-66-NH2@PPL are 18.96emu / g and 20.16emu / g, respectively. The modification of PPL has no significant change on the saturation magnetization strength of the material. The saturation magnetic field intensity of UiO-66-NH2 and UiO-66-NH2@PPL decreased, which may be due to the fact that during the modification of Fe3O4 and the synthesis of UiO-66, MOFs grew around Fe3O4 and wrapped the magnetic particles, mainly forming a material with Fe3O4 as the core. The content of magnetic particles per unit mass was reduced. However, after modification, they were still able to complete rapid separation and recovery in the water system within 30 seconds under the attraction of a magnet (2kOe), avoiding tedious and complicated centrifugation and filtration.
[0097] (5) The characteristic peaks and chemical structure of the hybrid material were analyzed by Fourier transform infrared absorption spectroscopy (FTIR). Figure 6 As shown. Figure 6 It can be seen that at 561.3cm -1 Fe-O bonds can be observed at 1089.8 cm -1 Si-O bonds can be observed at 1404.2 cm -1 There is an absorption band at 1564.3cm -1 and 1656.9cm -1 C=C bond was observed at 3414.1 cm -1 NH bonds were observed.
[0098] (6) The chemical elements and atomic chemical states of Fe3O4@SiO2@UiO-66 were analyzed by X-ray electron spectroscopy (XPS). Figure 7 As shown. Figure 7 The peaks at the binding energy of C, O, Zr, and Si elements can be observed, and no other impurity peaks are detected, indicating that the synthesized Fe3O4@SiO2@UiO-66 has good purity. After a narrow spectrum scan of the Si element in the sample, it was found that the binding energy position of the Si 2p orbital is located at 103.67eV, which belongs to Si oxide SiO2.
[0099] (7) The chemical elements and atomic chemical states of Fe3O4@SiO2@UiO-66-NH2 were analyzed by X-ray electron spectroscopy (XPS). Figure 8 As shown. Figure 8 The peaks at the binding energy of C, O, Zr, Si, and S elements can be observed, and no other impurity peaks are detected, indicating that the synthesized Fe3O4@SiO2@UiO-66-NH2 has good purity. After a narrow spectrum scan of the Si element in the sample, it was found that the binding energy position of the Si 2p orbital is located at 103.73eV, which belongs to Si oxide SiO2. After a narrow spectrum scan of the N element, it was found that the binding energy position of the N 1s orbital is located at 399.24eV, which belongs to the bond energy C-NH2, indicating that the N element in the sample exists in the form of -NH2.
[0100] (8) The chemical elements and atomic chemical states of the Fe3O4@SiO2@UiO-66-NH2@PPL spherical core-shell magnetic composites were analyzed by X-ray electron spectroscopy (XPS). Fig. 9 As shown. Fig. 9 Spectral peaks can be observed at the binding energy of C, O, Zr, Si, S, N, Na, and Cl elements. After a narrow spectrum scan of the Si element in the sample, it was found that the binding energy position of the Si 2p orbital was located at 103.73 eV, which was attributed to Si oxide SiO2. After a narrow spectrum scan of the N element, it was found that the binding energy position of the N 1s orbital was located at 399.24 eV, which was attributed to the bond energy C-NH2, indicating that the N element in the sample exists in the form of -NH2. After modifying PPL, peaks of Na and Cl elements were found, which may come from PPL and buffer PBS.
[0101] (9) Based on the above results, it can be seen that the present invention successfully prepared Fe3O4@SiO2@UiO-66-NH2@PPL spherical core-shell magnetic composite materials.
[0102] (B) Physical and chemical properties of Fe3O4@SiO2@UiO-66-NH2@PPL spherical core-shell magnetic composite materials prepared in Example 1 and Example 2:
[0103] (1) The adsorption-desorption isotherms of Fe3O4@SiO2@UiO-66-NH2@PPL spherical core-shell magnetic composites were recorded by nitrogen adsorption-desorption instrument, such as Fig.10 As shown. Fig.10 It can be seen that the nitrogen adsorption and desorption curves of the Fe3O4@SiO2@UiO-66-NH2@PPL spherical core-shell magnetic composite material show a typical combination of type III isotherms. Due to the occurrence of capillary condensation, the isotherm rises rapidly at medium relative pressure and has a hysteresis loop.
[0104] (2) The Brunauer-Emmett-Teller (BET) area, pore volume and pore size distribution were used to reveal the texture characteristics of the composite material, as shown in Table 2.
[0105] Table 2. Structural characteristic parameters of Fe3O4@SiO2@UiO-66-NH2@PPL
[0106]
[0107] As shown in Table 2, the specific surface area of Fe3O4@SiO2@UiO-66-NH2@PPL spherical core-shell magnetic composite material is 11.996 m 2 / g. The BJH (Barrett-Joyner-Halenda) pore size distribution curve shows that the pore size distribution range of Fe3O4@SiO2@UiO-66-NH2-PPL is very wide (>10nm), and the pore size is mainly concentrated at 3.63nm.
[0108] (C) Degradation effect of Fe3O4@SiO2@UiO-66-NH2@PPL spherical core-shell magnetic composite materials on ochratoxin A in Examples 4 to 6:
[0109] (1) HPLC was used to detect the residual ochratoxin A in the filtrate of Example 4. After the detection, the degradation rate of ochratoxin A was calculated. The results are as follows: Fig.11 As shown. Fig.11 (a) shows that as the degradation time increases, the degradation rate gradually increases. After 72 hours of degradation, the degradation rates of ochratoxin A under the conditions of the mass ratio of Fe3O4@SiO2@UiO-66-NH2 to porcine pancreatic lipase being 3:1, 2:1, 1:1, 1:2, and 1:3 are 58.60%, 69.07%, 73.16%, 62.78%, and 69.14%, respectively. Fig.11 From (b), we can see that Fig.11 The degradation curve of (a) conforms to the first-order kinetic model.
[0110] (2) HPLC was used to detect the residual ochratoxin A in the filtrate of Example 5. After the detection, the degradation rate of ochratoxin A was calculated. The results are as follows: Fig.12 As shown. Fig.12 (a) shows that as the degradation time increases, the degradation rate gradually increases. After 72 hours of degradation, when the fixed time of porcine pancreatic lipase is 5 hours, 7.5 hours, 10 hours, 12.5 hours, and 15 hours, the degradation rates of ochratoxin A are 37.09%, 48.07%, 49.82%, 34.48%, and 35.18%, respectively. Fig.12 From (b), we can see that Fig.12 The degradation curve of (a) conforms to the first-order kinetic model.
[0111] (3) HPLC was used to detect the residual ochratoxin A in the filtrate of Example 6. After the detection, the degradation rate of ochratoxin A was calculated. The results are as follows: Fig.13 As shown. Fig.13 (a) shows that with the extension of degradation time, the degradation rate gradually increases. After 72 hours of degradation, when the incubation temperature is 15℃, 20℃, 25℃, 30℃, 35℃, and 40℃, the degradation rates of ochratoxin A are 48.89%, 63.66%, 85.48%, 26.85%, and 21.45%, respectively. Fig.13 From (b), we can see that Fig.13 The degradation curve of (a) conforms to the first-order kinetic model.
[0112] (4) The BCA kit was mixed with an ELISA kit to detect the residual ochratoxin A in the filtrate of Example 5 and Example 6. The results showed that when the mass ratio of Fe3O4@SiO2@UiO-66-NH2 and porcine pancreatic lipase was 1:1 and the fixation time of porcine pancreatic lipase was 10 h, the adsorbed protein concentration of the composite material was the highest.
[0113] (5) Based on the above results, it can be seen that the mass ratio of Fe3O4@SiO2@UiO-66-NH2 and porcine pancreatic lipase, the fixation time of porcine pancreatic lipase, and the incubation temperature of the composite material and ochratoxin A will all affect the degradation rate of ochratoxin A. Among them, when the mass ratio of Fe3O4@SiO2@UiO-66-NH2 and porcine pancreatic lipase is 1:1, the fixation time of porcine pancreatic lipase is 7.5h and 10h at 20℃, and the incubation temperature of the composite material and ochratoxin A is 25℃, the Fe3O4@SiO2@UiO-66-NH2@PPL spherical core-shell magnetic composite material can achieve the best degradation effect.
[0114] (D) Degradation effect of Fe3O4@SiO2@UiO-66-NH2@PPL spherical core-shell magnetic composite material on mixed toxins in Example 7:
[0115] HPLC was used to detect the residual patulin and ochratoxin A in the filtrate of Example 7. The results showed that the degradation rate of patulin by the Fe3O4@SiO2@UiO-66-NH2@PPL spherical core-shell magnetic composite material was 35.62%, and the degradation rate of ochratoxin A was 47.67%.
Claims
1. A method for degrading toxins, It is characterized in that This method uses Fe 3 O 4 @SiO 2 @UiO-66-NH 2 @PPL spherical core-shell magnetic composite material degrades toxins; The toxin is a mixed toxin consisting of patulin and ochratoxin A; The Fe 3 O 4 @SiO 2 @UiO-66-NH 2 @PPL spherical core-shell magnetic composites made of Fe 3 O 4 @SiO 2 @UiO-66-NH 2 Materials and porcine pancreatic lipase composition; the Fe 3 O 4 @SiO 2 @UiO-66-NH 2 Material: Fe 3 O 4 @SiO 2 The nanoparticles are used as carriers, and zirconium is loaded on the carriers and modified with amino groups.
2. The method for degrading toxins according to claim 1, It is characterized in that The Fe 3 O 4 @SiO 2 @UiO-66-NH 2 The mass ratio of the material to porcine pancreatic lipase is (1:3) to (3:1).
3. The method for degrading toxins according to claim 1, It is characterized in that The Fe 3 O 4 @SiO 2 @UiO-66-NH 2 @The mass ratio of PPL spherical core-shell magnetic composite material, patulin and ochratoxin A is (10~20):(0.005~0.04):(0.005~0.04).
4. The method for degrading toxins according to claim 1, It is characterized in that The method specifically comprises the following steps: Step 1: Preparation of Fe 3 O 4 @SiO 2 @UiO-66-NH 2 @PPL spherical core-shell magnetic composites; Step 2: Degradation of mixed toxins: The mother solution of ochratoxin A was taken and slowly dried with nitrogen, and then dissolved with grape juice; the mother solution of patulin was taken and slowly dried with nitrogen, and then dissolved with apple juice; then the apple juice containing patulin and the grape juice containing ochratoxin A were mixed to obtain juice containing mixed toxins; finally, Fe 3 O 4 @SiO 2 @UiO-66-NH 2 @PPL spherical core-shell magnetic composite materials are added to the juice containing mixed toxins, and then incubated on a vortex oscillator. The incubation temperature is 20°C, the incubation speed is 100-300rpm, and the most preferred is 180rpm. The incubation time is 72 hours.
5. A method for degrading toxins, It is characterized in that This method uses Fe 3 O 4 @SiO 2 @UiO-66-NH 2 @PPL spherical core-shell magnetic composite material degrades toxins; The toxin is a single ochratoxin A; The Fe 3 O 4 @SiO 2 @UiO-66-NH 2 @PPL spherical core-shell magnetic composites made of Fe 3 O 4 @SiO 2 @UiO-66-NH 2 Materials and porcine pancreatic lipase composition; the Fe 3 O 4 @SiO 2 @UiO-66-NH 2 Material: Fe 3 O 4 @SiO 2 The nanoparticles are carriers, on which zirconium is loaded and modified with amino groups; The Fe 3 O 4 @SiO 2 @UiO-66-NH 2 The mass ratio of the material to porcine pancreatic lipase is (1:3) to (3:1); The Fe 3 O 4 @SiO 2 @UiO-66-NH 2 @The mass ratio of PPL spherical core-shell magnetic composite material and patulin is (10~20):(0.005~0.04).
6. The method for degrading toxins as claimed in claim 5, It is characterized in that The method specifically comprises the following steps: Step 1: Preparation of Fe 3 O 4 @SiO 2 @UiO-66-NH 2 @PPL spherical core-shell magnetic composites; Step 2: Degradation of ochratoxin A: Take the mother solution of ochratoxin A and slowly blow it dry with nitrogen, then dissolve it with grape juice, and then add Fe 3 O 4 @SiO 2 @UiO-66-NH 2 @PPL spherical core-shell magnetic composite material was added to grape juice containing ochratoxin A, and then incubated on a vortex oscillator at an incubation temperature of 15-40°C, an incubation speed of 100-300 rpm, and an incubation time of 72 hours.
7. The method for degrading toxins according to claim 4 or 5, It is characterized in that The step 1 specifically includes the following steps: Step 1.1, preparation of Fe 3 O 4 @SiO 2 Nanoparticles; Step 1.2, preparation of Fe 3 O 4 @SiO 2 @UiO-66-NH 2 Material: The Fe 3 O 4 @SiO 2 Nanoparticles, zirconium chloride and water are added to N, N-dimethylformamide and stirred to obtain an iron zirconium precursor mixture; 2,5-diaminoterephthalic acid is added to N, N-dimethylformamide to obtain a 2,5-diaminoterephthalic acid solution; the iron zirconium precursor mixture and the 2,5-diaminoterephthalic acid solution are mixed and stirred continuously until they are completely dissolved, and then the mixed system is heated at 120° C. for 24 hours, taken out, cooled to room temperature, and washed with water to obtain Fe 3 O 4 @SiO 2 @UiO-66-NH 2 Materials, finally Fe 3 O 4 @SiO 2 @UiO-66-NH 2 Material drying; Step 1.3, Immobilization of Porcine Pancreatic Lipase: The Fe 3 O 4 @SiO 2 @UiO-66-NH 2 The material, porcine pancreatic lipase and phosphate buffer solution were mixed; the mixture was then shaken at 20°C for 5 to 15 hours and then taken out, filtered and solid products were collected; finally, the solid products were washed with phosphate buffer solution and freeze-dried overnight to obtain Fe 3 O 4 @SiO 2 @UiO-66-NH 2 @PPL spherical core-shell magnetic composites.
8. Fe as claimed in claim 7 3 O 4 @SiO 2 @UiO-66-NH 2 @PPL Preparation method of spherical core-shell magnetic composite material, It is characterized in that The step 1.1 is specifically as follows: Fe 3 O 4 The nanoparticles were ultrasonically dispersed in distilled water, and then ammonia and ethanol were added and stirred to obtain an iron precursor mixture; ethyl tetrasilicate was dissolved in ethanol and stirred until the mixture was uniform to obtain an ethyl tetrasilicate solution; the ethyl tetrasilicate solution was added to the iron precursor mixture and stirred, and then the solution was separated by an external magnet and washed with distilled water and ethanol several times to obtain Fe 3 O 4 @SiO 2 Nanoparticles, and finally Fe 3 O 4 @SiO 2 Nanoparticle drying.
9. A kind of Fe 3 O 4 @SiO 2 @UiO-66-NH 2 @PPL spherical core-shell magnetic composite material, It is characterized in that The composite material consists of Fe 3 O 4 @SiO 2 @UiO-66-NH 2 Materials and porcine pancreatic lipase composition; the Fe 3 O 4 @SiO 2 @UiO-66-NH 2 Material: Fe 3 O 4 @SiO 2 The nanoparticles are used as carriers, and zirconium is loaded on the carriers and modified with amino groups.
10. A Fe as claimed in claim 9 3 O 4 @SiO 2 @UiO-66-NH 2 @PPL Preparation method of spherical core-shell magnetic composite material, It is characterized in that The method specifically comprises the following steps: Step 1.1, preparation of Fe 3 O 4 @SiO 2 Nanoparticles; Fe 3 O 4 The nanoparticles were ultrasonically dispersed in distilled water, and then ammonia and ethanol were added and stirred to obtain an iron precursor mixture; ethyl tetrasilicate was dissolved in ethanol and stirred until the mixture was uniform to obtain an ethyl tetrasilicate solution; the ethyl tetrasilicate solution was added to the iron precursor mixture and stirred, and then the solution was separated by an external magnet and washed with distilled water and ethanol several times to obtain Fe 3 O 4 @SiO 2 Nanoparticles, and finally Fe 3 O 4 @SiO 2 Nanoparticle drying; Step 1.2, preparation of Fe 3 O 4 @SiO 2 @UiO-66-NH 2 Material: The Fe 3 O 4 @SiO 2 Nanoparticles, zirconium chloride and water are added to N, N-dimethylformamide and stirred to obtain an iron zirconium precursor mixture; 2,5-diaminoterephthalic acid is added to N, N-dimethylformamide to obtain a 2,5-diaminoterephthalic acid solution; the iron zirconium precursor mixture and the 2,5-diaminoterephthalic acid solution are mixed and stirred continuously until they are completely dissolved, and then the mixed system is heated at 120° C. for 24 hours, taken out, cooled to room temperature, and washed with water to obtain Fe 3 O 4 @SiO 2 @UiO-66-NH 2 Materials, finally Fe 3 O 4 @SiO 2 @UiO-66-NH 2 Material drying; Step 1.3, Immobilization of Porcine Pancreatic Lipase: The Fe 3 O 4 @SiO 2 @UiO-66-NH 2 The material, porcine pancreatic lipase and phosphate buffer solution were mixed; the mixture was then shaken at 20°C for 5 to 15 hours and then taken out, filtered and solid products were collected; finally, the solid products were washed with phosphate buffer solution and freeze-dried overnight to obtain Fe 3 O 4 @SiO 2 @UiO-66-NH 2 @PPL spherical core-shell magnetic composites.
